Identifying Racism and Racial Stereotypes in Rainbow Rowell’s Eleanor and Park - Sofyani, Rizki Amelia; Rangkuti, Rahmadsyah; Lubis, Masdiana (Politeknik Harapan Bangsa Surakarta, 2022)
The study aims to identify racism and racial stereotype in text structure, social cognition, and social context of Rainbow Rowell’s Eleanor and Park. The study uses qualitative descriptive design and conducts Teun A. van Dijk’s socio-cognitive approach to analyze words, phrases and sentences which contain racism and racial stereotype in Eleanor & Park. The result shows that racism in Eleanor and Park novel are in the form of implicit, explicit, internalized racism, and fetishism of Asian. The racial stereotypes in the novel are the stereotypes of Asian physical features, namely the description of a short body, slanted eyes, weak and helpless appearances, and also the use of the word